Identification of predominant motor skills at the level of girls handball teams juniors III - Postelnicu, M.-G.; Mihaila, I.; Bastiurea, E. (Science, Movement & Health, 2020)
Objective. The purpose of this study is to identify the main motor skills involved in performing specific motor actions for junior girl'shandball players aged 13-15.This was done on the basis of a sociological survey conducted through a questionnaire consisting of a series of questions formulated and aimed at identifying the degree of involvement, role and importance of developing motor skills in handball teams, juniors III. During the survey questionnaire, 55 trainers with handball specialization and theoreticians from the faculties of physical education and sports with handball specialization were interviewed, the questionnaires being distributed in letter and online format. Methods.The research methods used during this study were: the method of analyzing the specialized and interdisciplinary literature, the pedagogical observation method, the survey method, the statistical-mathematical method, the graphical method and the tabel method. Results.The answers obtained were statistically processed and graphically represented in order to interpret them and draw conclusions. Conclusions.The conclusions drawn from the interpretation of the answers of the interviewed specialists indicate that it is necessary to implement a unitary training concept specific to each category of juniors, as well as to apply training methods in accordance with the current requirements of the performance handball. At the same time, the general conclusion that emerges, highlights the fact that at each level of performance there are certain motor qualities that are acted upon as a priority, based on the principles of interference and transfers on the other motor qualities.